Effect of trust, risk perception and diffusion of innovation on the adoption/use of internet banking in Indonesia - Diana Triwardhani; Dahlia Br Pinem; Yuliniar Yuliniar; Lina Aryani; Bernadin Bernadin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to prove the effect of trust, risk perception, and diffusion of innovation on the adoption or use of Internet banking in Indonesia. The research method used is quantitative, with a sample of 500 people from Jakarta, Bandung, Semarang, and Surabaya, and data collection using a questionnaire. The results of this study state that confidence, perceived risk, and diffuse innovation affect the use of Internet banking. In addition, this study also contributes to stakeholder theory. The existence of concern for the environment affects the company's ability. This study shows that the environment can increase customer trust. Therefore, companies must pay attention to the interests of interested parties by putting them in the framework of principles and making decisions to support the achievement of the company's goals, namely company stability and guaranteed business continuity and trust.